Community Based Eco-Tourism Development Strategy on Sebesi Island, South Lampung - Murni, Murni; Putra, Fadillah; Sanusi, Anwar (Graduate School, Universitas Brawijaya, 2022)
The advantages of tourism potential in the Lampung Region include the natural beauty of the land and sea, which is surrounded by green hills and mountains overgrown with various species of flowers and trees. Cultural diversity and local wisdom also look unique and interesting. One of the interesting areas to be researched is Sebesi Island, South Lampung Regency, which is located between the islands of Java and Sumatra, so it becomes a strategic area for development. This study aims to determine the strategy for developing community-based ecotourism in Sebesi Island, South Lampung. The object of this research is Tejang village, which has four sub-villages, namely Bangunan, Inpres, Segenom, and Regahan Lada. Before conducting the research, the researcher assessed the tourism component of Sebesi Island with 4A, attractions, facilities, accessibilities, and ancillary services. The theory used for ecotourism research is the theory of Cobbinah, namely the principle of tourism, the principle of nature conservation, the principle of preservation and cultural preservation, the principle of economics, and the principle of community participation. This research used mixed methods with a dominant use of qualitative analysis. It is supported by quantitative analysis as a reinforcement for supply aspects of analysis and SWOT analysis, or sequential exploratory design. The sample of this research uses purposive sampling of parties related to the development process. While determining the strategy for developing ecotourism on Sebesi Island, some data analysis is needed, including supply and demand analysis to determine the value of development feasibility and SWOT analysis to determine the right development strategy. The determination of the SWOT variable consisting of internal and external factors then provides an assessment of each element that is considered to influence the development of ecotourism on Sebesi Island. The next step is to determine the position of alternative strategies from the SWOT analysis consisting of strengths – opportunities (SO) and strengths – threats (ST), weakness - opportunities (WO) and weakness - threats (WT), and the last step is to create an 8 Quadrant SWOT matrix to determine what strategy to implement. The results of this study indicate that the Rapid Growth Strategy can be used. The strategy is to take advantage of various opportunities for the development of Sebesi Island as an ecotourism area in a responsible manner while maintaining its function by improving visitor services based on Standard Operational Procedures and collaborating with related parties in preparing ecotourism activities. It is to increase tourist interest and the income of local residents. Keywords: Ecotourism, Community, Development Strategy, Sebesi Island, SWOT